Plataformas de mídias sociais como espaços de ação em rede: reconhecimento e cidadania no grupo mulheres unidas contra Bolsonaro - Bulegon, Bruna Martins (2023)
This study proposes to investigate social media platforms as spaces for social practices in the #elenão digital networked action (DNA), taking as a case study the group Mulheres Unidas Contra Bolsonaro (MUCB) on the Facebook platform. Using the traces left by interactional dynamics, we seek to analyze how these interactions contributed for the formation of a women's mobilization in Brazil in 2018. In addition, we examine how the platform is suitable for this purpose and how it modulates these appropriations. The understanding of network action is based on the type of social bond built through interactions. Our analysis is based on the perception of how social practices and alliance patterns develop a space of citizenship for women within this platform. The objectives of this study include mapping the ways in which the #elenão movement manifests itself in the MUCB group on Facebook, identifying the context of the digital network action, tracing the historical, social and political scenario of #elenão, mapping the interactional dynamics in the MUCB group and identifying the social practices and alliance patterns developed both for building social ties and for forming network density. We also analyzed how the political network action can generate a community among the participants, through the constructed graphs, and we established relationships between the social practices of the group to understand the feeling of community and the identification among the participants. To achieve these goals, we employ a digital methods approach that includes ta textual analysis through Iramuteq and the creation of graphs to represent the infrastructure of these relationships. To support our research, we explore theories related to social media platforms, digital network action, social bonding, web platformization, and social movements. We thus realize that we can consider #elenão, specifically the Grupo Mulheres Unidas Contra Bolsonaro, as an action in a political digital network mobilized within the modulations of social media platforms.